Direct Democracy Integrity in Modern Authoritarian Systems: The Constitutional Referendum in Turkey 2017 and Russian Plebiscite in 2020 - Kersting, Norbert; Zavadskaya , Margarita; Magne , Tiphaine (Politics of the Low Countries, 2025)
Modern authoritarian regimes have implemented a relatively large number of referendums in recent decades. These have had important consequences for institutional change. Applying the new Direct Democracy Integrity Index to the Turkish constitutional referendum in 2017 and the Russian constitutional referendum in 2020, this analysis determines whether these plebiscites fulfil the standards of integrity and respect the rights of oppositional parties and minorities. We found that the level of integrity was lower during the pre-election period than during the election or the post-election period. We observe that modern authoritarian systems such as Russia (in 2020) use strategies of mobilisation, activism and even modern forms of deliberative democracy. However, their strategies are characterised by propaganda. In contrast, authoritarian regimes (such as Turkey) are still implementing strategies of repression which lead to passivity, disengagement and apathy. Both have strong implications for the integrity of referendums.